Visual Notation as a Narrative Development of the Perception of Change - Croft, Michael (Architecture Image Studies, 2021)
The Casa da Musica on Av. da Boavista, Porto, is a commanding iconic building at first sight in its own space. Two roads from the building, tangential to Rotunda da Boavista, is a huge area of cleared land for a new development on the site of the former Boavista Railway Station. On the next tangential road is a café whose customers look across the road towards the exposure of the Casa da Musica to a surprising comparison of the building’s roof incline with the regular urban skyline. The article takes this detail as an instance of the potentiality to be found in casual perceptions that can be encountered in moments of urban change that punctuate a city’s life. The author’s means of visualising such perception is through a form of visual notation. Such notations as the author presents in illustration of his argument employ a transitional mode of visualising that is instructional to the viewer that can communicate the transitory perception of change pertinent to the site under consideration. The visuals were being made as the first draft of the article was being written. Since the article started to suggest a direction for what started as focused recreational activity, the visuals culminate in, and the possibility is posed, of how the Casa… could itself cast a net across and accommodate the void space temporarily opened up by the development site.